Ինքնիշխանության պահպանման և փոխակերպման միտումները Եվրոպական Միությունում - Խոջայան, Լուսինե
В данной статье проблема государственного суверенитета рассматривается на примере европейской интеграции Франции. Хотя Франция является первопроходцем в процессе европейской интеграции и представлена на всех уровнях (интеграции), тем не менее, ее европейская политика не лишена противоречивости. В статье подробно представлено, что на разных этапах политики европейской интеграции Франции доминировал межгосударственный подход, и придавалось большое значение проблеме защиты национальных интересов. The article considers the problem of state sovereignty on the example of European integration of France. Although France is a pioneer in the European integration process and it is represented at all levels of integration, its European policy is not without contradictions. It is argued in the article that had to keep a fragile balance between further integration and national sovereignty. At different stages of European integration in the policy of France dominated the intergovernmental approach, and the protection of national interests had a great importance.
Keywords: Քաղաքագիտություն